Metal carbon-based composite catalyst as well as preparation method and application thereof
By mixing P123 with soluble metal salts with high temperature heat solution, the high -efficiency metal carbon -based composite catalyst is prepared, the problem of insufficient activity and durability in the precious metal catalyst in OER, and achieved efficient oxygen repayment catalytic effects.
Patent Information
- Application Number
- CN202411526061.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-28
AI Technical Summary
In the prior art, the activity and durability of noble metal-based electrocatalysts in oxygen reduction reaction (OER) are insufficient, resulting in limited application in the process of water cracking and hydrogen production, and lack of efficient and low-cost non-precious metal catalysts.
By mixing the polyethylene (ethylene oxide-oxide-ethylene oxide) three-stage coatings (P123) with soluble cobalt salt, iron salt, nickel salt to prepare metal carbon-based composite catalysts, and through high temperature heat Solution optimize its structure and performance.
The prepared metal carbon -based composite catalysts have significantly increased their activity in the oxygen reaction reaction, the excess potential is reduced, the catalyst synthesis process is simple, it is easy to repeat, and the particles are not easy to gather, which improves the stability and efficiency of the catalyst.
Smart Images

Figure CN119372703A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of water oxidation catalytic preparation, and specifically relates to a metal-carbon based composite catalyst and a preparation method and application thereof. Background Art
[0002] Hydrogen energy has high energy density and environmental friendliness, and is widely regarded as a promising energy carrier for achieving energy upgrading. Among various hydrogen production technologies, electrocatalytic water splitting stands out due to its multiple advantages such as zero pollution, high product purity, and simple operation. Generally speaking, water splitting involves two half reactions: anodic oxygen evolution reaction (OER) and cathodic hydrogen evolution reaction (HER). Compared with HER, OER has higher energy requirements and thermodynamic barriers due to its slow multi-proton coupled electron transfer process. Although noble metal-based electrocatalysts (such as RuO2 and IrO2) have shown impressive activity in OER, their widespread application is hindered by their scarcity and durability. Therefore, there is an urgent need to construct earth-abundant transition metal-based electrocatalysts to replace noble metal-based electrocatalysts, so as to take a step towards large-scale water splitting hydrogen production.
[0003] So far, people have been committed to developing non-precious metal OER catalysts with excellent performance and low price. Compounds such as Cr, Co, and Fe are considered to be candidates with high value for improving the activity of oxygen evolution reaction. Among non-precious metal catalysts, Fe, Co, and Ni-based catalysts have attracted much attention due to their abundant reserves in the world. In recent years, combining two or more catalytic materials to construct heterostructures has become an effective strategy to improve the activity of catalysts. The formation of composite structures can not only effectively promote interfacial electron transport and regulate the adsorption free energy of reaction species, but also produce new interfacial structures by changing the composition and crystal phase of the structure, thereby achieving efficient oxygen evolution catalytic function. In addition, the preparation of multi-component transition metal (such as Co, Ni, and Fe) sulfides, phosphides, carbides, etc. by element doping is also a good engineering strategy. By controlling and designing defect engineering to regulate active centers, great success has been achieved, showing good electrocatalytic activity, thereby improving the oxygen evolution activity of OER. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a metal-carbon based composite catalyst.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0008] A method for preparing a metal-carbon-based composite catalyst, comprising:
[0009] The poly(ethylene oxide-propylene oxide-ethylene oxide) three-stage co-embedded compound (abbreviation: P123) and a soluble metal salt are dissolved in water to obtain a mixed solution, and the mixed solution is dried to obtain a solid gel; the solid gel is pyrolyzed at high temperature under a nitrogen atmosphere to obtain a metal-carbon-based composite catalyst; the soluble metal salt is one or more of a soluble cobalt salt, a soluble iron salt, and a soluble nickel salt.
[0010] As a preferred embodiment of the preparation method of the present invention, the soluble cobalt salt is cobalt acetylacetonate, the soluble iron salt is iron acetylacetonate, and the soluble nickel salt is nickel acetylacetonate.
[0011] As a preferred embodiment of the preparation method of the present invention, the ratio of P123 to soluble metal salt is 2g:1-5mmol.
[0012] As a preferred embodiment of the preparation method of the present invention, the molar ratio of the soluble cobalt salt, the soluble iron salt and the soluble nickel salt is (1-4): (0-2): (0-2).
[0013] Further, the molar ratio of the soluble cobalt salt, the soluble iron salt, and the soluble nickel salt is 2:(0.5-2):(0-1.5);
[0014] Furthermore, the molar ratio of the soluble cobalt salt, the soluble iron salt and the soluble nickel salt is 2:1:(0-1.5).
[0015] Furthermore, the molar ratio of the soluble cobalt salt, the soluble iron salt and the soluble nickel salt is 2:1:(0-1).
[0016] Most preferably, the molar ratio of the soluble cobalt salt, the soluble iron salt and the soluble nickel salt is 2:1:1.
[0017] As a preferred embodiment of the preparation method of the present invention, the temperature of the high-temperature pyrolysis is 600-800°C, preferably 600-700°C, and more preferably 700°C.
[0018] As a preferred embodiment of the preparation method of the present invention, the high temperature pyrolysis time is 3 hours, and the heating rate is 5°C min -1 .
[0019] Another object of the present invention is to overcome the deficiencies in the prior art and provide a metal-carbon-based composite catalyst prepared by the above preparation method.
[0020] In some exemplary embodiments of the present invention, the metal-carbon-based composite catalyst includes NiFe alloy, FeCo alloy and carbon.
[0021] Another object of the present invention is to overcome the deficiencies in the prior art and provide a metal-carbon-based composite catalyst for use as an oxygen reduction catalyst.
[0022] More specifically, the above-mentioned metal-carbon-based composite catalyst is evenly mixed with activated carbon, anhydrous ethanol and Nafion solution to obtain a uniformly dispersed ink, which is then dropped onto the surface of a glassy carbon electrode to prepare a catalyst-loaded glassy carbon electrode as a working electrode, a KCl-saturated Ag / AgCl electrode as a reference electrode, and a carbon rod as a counter electrode to construct a three-electrode system for electrocatalytic water oxidation.
[0023] The mass ratio of the catalyst to the activated carbon is 1:1; the volume ratio of anhydrous ethanol to the Nafion solution is 95:5; and in the ink, the mass concentration of the catalyst is 2 mg / mL.
[0024] The catalyst loading on the glassy carbon electrode is 0.25 mg cm -2 .
[0025] Beneficial effects of the present invention:
[0026] (1) The present invention provides a metal-carbon-based composite catalyst Co2Fe1Ni x / C preparation method, through high temperature pyrolysis conditions, P123 and acetylacetonate cobalt, acetylacetonate iron, acetylacetonate nickel mixed pyrolysis, to prepare a high-efficiency oxygen evolution reaction catalyst, the catalyst synthesis process is simple, easy to repeat; at the same time, the prepared catalyst particles are not easy to agglomerate, thereby improving the oxygen evolution performance of the catalyst.
[0027] (2) The present invention uses P123 as a carbon source and regulator, further regulates the ratio of cobalt, iron and nickel, and obtains an alloy and carbon-based composite catalyst, achieving a good synergistic catalytic effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0029] Figure 1 This is a comparison chart of the XRD of the catalyst in Example 1 of the present invention.
[0030] Figure 2 Co2Fe1Ni with different molar amounts of nickel prepared by the present invention x LSV comparison chart of / C.
[0031] Figure 3 This is a LSV comparison diagram of Co2Fe1Ni1 / C calcined at different temperatures prepared in the present invention.
[0032] Figure 4 The molar amount of Co2Fe prepared by the present invention is different from that of metallic iron x LSV comparison chart of / C.
[0033] Figure 5 is the molar amount of Co of different metal cobalt prepared in the present invention x LSV comparison chart of / C. DETAILED DESCRIPTION
[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0035] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0036] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0037] Evaluation of water oxidation reaction performance in the embodiments of the present invention: Tested by electrochemical workstation: First, a glassy carbon electrode (area 0.126 cm) was polished with a small amount of 1 μm aluminum oxide polishing powder. 2) until its surface is bright, and then rinse with deionized water and ethanol, and dry in the shade at room temperature. Weigh 2 mg of catalyst and 2 mg of activated carbon into a sample tube, add 950 μL of anhydrous ethanol and 50 μL of Nafion solution, and obtain a uniformly dispersed ink after ultrasonic treatment. Then take 15.8 μL of ink and drop it on the surface of the glassy carbon electrode, dry in the shade at room temperature for later use. The loading amount of catalyst on the electrode surface is 0.25 mg cm -2 ; The electrochemical performance of the catalyst at room temperature was tested in a three-electrode system, with a glassy carbon electrode (GC) loaded with the catalyst as the working electrode, a KCl-saturated Ag / AgCl electrode as the reference electrode, and a carbon rod as the counter electrode.
[0038] The RDE speed of LSV test is 1600rpm, the test voltage range is -0.023~0.977V, and the scanning speed is 5mV / s.
[0039] The LSV polarization curve can be used to obtain important parameters of OER catalyst performance: 10 mA cm -2 Overpotential at current density.
[0040] 10mA cm -2 The lower the overpotential under current density, the higher the electrocatalytic water oxidation activity of the catalyst.
[0041] The raw materials in the embodiments of the present invention are all common commercially available products. Example 1
[0042] Co2Fe1Ni x Preparation of / C materials: Weigh 2 g of P123 and place it in a beaker. Pour 30 mL of deionized water into the beaker and stir evenly with a magnetic stirrer to obtain a colorless solution A. Take 2 mmol of cobalt (II) acetylacetonate and place it in colorless solution A, and stir with a magnetic stirrer to dissolve it completely to obtain a pink solution B; Take 1 mmol of iron acetylacetonate and place it in pink solution B, and stir with a magnetic stirrer to dissolve it completely to obtain a red solution C; Take 1 mmol of nickel acetylacetonate and place it in the red solution C and stir it with a magnetic stirrer for 3 h to obtain a red solution D; Place the red solution D in a 60°C water bath and dry it to a solid gel F; Then, the solid gel F was placed in a tubular furnace under a nitrogen atmosphere at 700°C and calcined for 3 h to obtain a black product G; The obtained black product G was put into an agate mortar and ground evenly, and the obtained black powder was Co2Fe1Ni1 / C.
[0043] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 2 ; It can be seen that the Co2Fe1Ni1 / C catalyst has the highest electrocatalytic water oxidation performance, and the electrocatalytic water oxidation is -2 The overpotential is 325mV. Example 2
[0044] The same synthesis method was used as in Example 1, except that the molar amount of nickel acetylacetonate was changed to 0.5 mmol, and the other moles remained unchanged. The final product was named Co2Fe1Ni 0.5 / C.
[0045] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 2 ; It can be seen that Co2Fe1Ni 0.5 The / C catalyst has the highest electrocatalytic water oxidation performance at 10 mA cm -2 The overpotential is 373 mV. Example 3
[0046] The same synthesis method was used as in Example 1, except that the molar amount of nickel acetylacetonate was changed to 1.5 mmol, and the other moles remained unchanged. The final product was named Co2Fe1Ni 1.5 / C.
[0047] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 2 ; It can be seen that Co2Fe1Ni 1.5 The / C catalyst has the highest electrocatalytic water oxidation performance at 10 mA cm -2 The overpotential is 372 mV. Example 4
[0048] The same synthesis method was used as in Example 1, except that the molar amount of nickel acetylacetonate was changed to 2 mmol, and the other contents remained unchanged. The final product was named Co2Fe1Ni2 / C.
[0049] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 2 ; It can be seen that the Co2Fe1Ni2 / C catalyst has the highest electrocatalytic water oxidation performance, and the electrocatalytic water oxidation is -2 The overpotential is 385mV. Example 5
[0050] The same synthesis method was used as in Example 1, except that the high temperature calcination temperature was changed to 600°C, and other conditions remained unchanged. The final product was named Co2Fe1Ni1 / C-600.
[0051] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 3 It can be seen that the Co2Fe1Ni1 / C-600 catalyst has the highest electrocatalytic water oxidation performance. -2 The overpotential is 372 mV. Example 6
[0052] The same synthesis method was used as in Example 1, except that the high temperature calcination temperature was changed to 800°C, and other conditions remained unchanged. The final product was named Co2Fe1Ni1 / C-800.
[0053] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 3 It can be seen that the Co2Fe1Ni1 / C-800 catalyst has the highest electrocatalytic water oxidation performance. -2 The overpotential is 396 mV. Example 7
[0054] Preparation of Co2Fe1 / C material: Weigh 2 g of P123 and place it in a beaker. Pour 30 mL of deionized water into the beaker and stir evenly with a magnetic stirrer to obtain a colorless solution A. Take 2 mmol of cobalt (II) acetylacetonate and place it in colorless solution A, and stir with a magnetic stirrer to dissolve it completely to obtain a pink solution B; Take 1 mmol of iron acetylacetonate and place it in pink solution B, and stir with a magnetic stirrer to dissolve it completely to obtain a red solution C; Place the red solution C in a 60°C water bath and dry it to a solid gel F; Then, the solid gel F was placed in a tubular furnace under a nitrogen atmosphere at 700°C and calcined for 3 h to obtain a black product D. The obtained black product D was put into an agate mortar and ground evenly to obtain a black powder, which was Co2Fe1 / C.
[0055] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 4 ; It can be seen that the Co2Fe1 / C catalyst has the highest electrocatalytic water oxidation performance, and the electrocatalytic water oxidation is -2 The overpotential is 366 mV. Example 8
[0056] The same synthesis method was used as in Example 7, except that the molar amount of ferric acetylacetonate was changed to 0.5 mmol, and the other moles remained unchanged. The final product was named Co2Fe 0.5 / C.
[0057] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 4 ; It can be seen that Co2Fe 0.5 The / C catalyst has the highest electrocatalytic water oxidation performance at 10 mA cm -2 The overpotential is 389 mV. Example 9
[0058] The same synthesis method was used as in Example 7, except that the molar amount of ferric acetylacetonate was changed to 1.5 mmol, and the other moles remained unchanged. The final product was named Co2Fe 1.5 / C.
[0059] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 4 ; It can be seen that Co2Fe 1.5 The / C catalyst has the highest electrocatalytic water oxidation performance at 10 mA cm -2 The overpotential is 379 mV. Example 10
[0060] The same synthesis method was used as in Example 7, except that the molar amount of ferric acetylacetonate was changed to 2 mmol, and the other contents remained unchanged. The final product was named Co2Fe2 / C.
[0061] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 4 ; It can be seen that the Co2Fe2 / C catalyst has the highest electrocatalytic water oxidation performance, and the electrocatalytic water oxidation is -2 The overpotential is 384 mV. Embodiment 11
[0062] Preparation of Co2 / C materials: Weigh 2 g of P123 and place it in a beaker. Pour 30 mL of deionized water into the beaker and stir evenly with a magnetic stirrer to obtain a colorless solution A. Take 2 mmol of cobalt (II) acetylacetonate and place it in colorless solution A, and stir with a magnetic stirrer to dissolve it completely to obtain a pink solution B; Place the red solution B in a 60°C water bath and dry it to a solid gel F; Then, the solid gel F was placed in a tubular furnace under a nitrogen atmosphere at 700°C and calcined for 3 h to obtain a black product C. The obtained black product C was put into an agate mortar and ground evenly, and the obtained black powder was Co2 / C.
[0063] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 5 ; It can be seen that the Co2 / C catalyst has the highest electrocatalytic water oxidation performance, and the electrocatalytic water oxidation is -2 The overpotential is 395mV. Example 12
[0064] The same synthesis method was used as in Example 11, except that the molar amount of cobalt acetylacetonate was changed to 1 mmol, and the other contents remained unchanged. The final product was named Co1 / C.
[0065] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 5 ; It can be seen that the Co1 / C catalyst has the highest electrocatalytic water oxidation performance, and the electrocatalytic water oxidation is -2 The overpotential is 548 mV. Embodiment 13
[0066] The same synthesis method was used as in Example 11, except that the molar amount of cobalt acetylacetonate was changed to 3 mmol, and the other contents remained unchanged. The final product was named Co3 / C.
[0067] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 5 ; It can be seen that the Co3 / C catalyst has the highest electrocatalytic water oxidation performance, and the electrocatalytic water oxidation is -2 The overpotential is 417 mV. Embodiment 14
[0068] The same synthesis method was used as in Example 11, except that the molar amount of cobalt acetylacetonate was changed to 4 mmol, and the other contents remained unchanged. The final product was named Co4 / C.
[0069] After the above catalyst was prepared into a working electrode for electrocatalytic water oxidation test, see Figure 5 ; It can be seen that the Co4 / C catalyst has the highest electrocatalytic water oxidation performance, and the electrocatalytic water oxidation is -2 The overpotential is 435mV.
[0070] Preferably, the amount of cobalt acetylacetonate is 2 mmol, the amount of iron acetylacetonate is 1 mmol, the amount of nickel acetylacetonate is 1 mmol, the amount of P123 is 1 mmol, the calcination temperature is 700°C, and the heating rate is 5°C / min to achieve the best water oxidation catalytic effect.
[0071] The invention prepares a high-efficiency water oxidation catalyst by preparing a mixture of P123 and cobalt acetylacetonate, iron acetylacetonate and nickel acetylacetonate at room temperature and then pyrolyzing the mixture at high temperature. The catalyst synthesis process is simple and easy to repeat. The prepared catalyst particles are not easy to agglomerate and have high oxygen evolution catalytic activity and conductivity.
[0072] The present invention compounds P123, cobalt acetylacetonate, iron acetylacetonate and nickel acetylacetonate to achieve a good synergistic catalytic effect; at the same time, the compounding ratio and calcination temperature are optimized to achieve the best water oxidation performance.
[0073] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A method for preparing a metal-carbon based composite catalyst, characterized in that: The steps include: The three-stage poly(ethylene oxide-propylene oxide-ethylene oxide) co-embedded product and a soluble metal salt are dissolved in water to obtain a mixed solution, and the mixed solution is dried to obtain a solid gel; the solid gel is pyrolyzed at high temperature under an inert atmosphere to obtain a metal-carbon-based composite catalyst; the ratio of the three-stage poly(ethylene oxide-propylene oxide-ethylene oxide) co-embedded product to the soluble metal salt is 2g:1-5mmol; the soluble metal salt is one or more of a soluble cobalt salt, a soluble iron salt, and a soluble nickel salt.
2. The method for preparing the metal-carbon based composite catalyst according to claim 1, characterized in that: The soluble cobalt salt is cobalt acetylacetonate, the soluble iron salt is iron acetylacetonate, and the soluble nickel salt is nickel acetylacetonate.
3. The method for preparing the metal-carbon based composite catalyst according to claim 1, characterized in that: The molar ratio of the soluble cobalt salt, the soluble iron salt and the soluble nickel salt is 1-4:0-2:0-2.
4. The method for preparing the metal-carbon based composite catalyst according to claim 3, characterized in that: The molar ratio of the soluble cobalt salt, the soluble iron salt and the soluble nickel salt is 2:0.5-2:0-1.
5.
5. The method for preparing the metal-carbon based composite catalyst according to claim 1, characterized in that: The molar ratio of the soluble cobalt salt, the soluble iron salt and the soluble nickel salt is 2:1:0-1.
5.
6. The method for preparing the metal-carbon based composite catalyst according to claim 1, characterized in that: The molar ratio of the soluble cobalt salt, the soluble iron salt and the soluble nickel salt is 2:1:0-1.
7. The method for preparing the metal-carbon based composite catalyst according to claim 1, characterized in that: The molar ratio of the soluble cobalt salt, the soluble iron salt and the soluble nickel salt is 2:1:
1.
8. The method for preparing the metal-carbon based composite catalyst according to claim 1, characterized in that: The inert atmosphere of the high-temperature pyrolysis is nitrogen, the pyrolysis temperature is 600-800° C., and the pyrolysis time is 3 hours.
9. The metal-carbon based composite catalyst prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the metal-carbon-based composite catalyst according to claim 9 as an oxygen evolution reaction catalyst.